Exploring the Multifaceted Landscape of English-Medium Instruction: Students' Perspectives and Challenges at the University of Kutai Kartanegara - Rahman , Andika; M. Bahri Arifin; Ping, Maria Teodora (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2024)
This mixed-methods study investigated students' perceptions of using English as a Foreign Language (EFL) as a medium of instruction at the University of Kutai Kartanegara. Data were collected through a questionnaire (n=25) and semi-structured interviews. Quantitative results showed an overall positive perception, with a mean score of 71.38 on the questionnaire. However, qualitative findings revealed nuances in students' experiences. While most enjoyed learning English and appreciated lecturers' engaging teaching styles, some faced difficulties with comprehension due to lecturers' delivery or their students’ proficiency levels. Students had varied engagement in extracurricular English activities. Interactions in English with lecturers facilitated language development, but peer interactions were limited. Most deemed English suitable for language classes but had concerns about its exclusive use in non-language courses given varying proficiencies. Lecturers employed motivational strategies like emphasizing English's importance and suggesting practical activities, but implementation of English-medium instruction was inconsistent. Benefits included improving skills like presentations and vocabulary, but challenges included inadequate proficiency, lack of motivation, workload concerns, and limited materials. The research contributes valuable insights for policymakers, educators, and researchers in English language education and international higher education, emphasizing the importance of creating inclusive learning environments that support both language acquisition and academic content mastery.